1998
DOI: 10.1111/1469-7610.00305
|View full text |Cite
|
Sign up to set email alerts
|

Research Update: Childhood‐onset Schizophrenia: Implications of Clinical and Neurobiological Research

Abstract: Childhood-onset schizophrenia is a rare, clinically severe form of schizophrenia, which is associated with disrupted cognitive, linguistic, and social development well before the appearance of frank psychotic symptoms. This disruption of multiple developmental domains signals the important opportunity these patients present for examining neurodevelopmental and other etiologic hypotheses of schizophrenia. The present research update reviews studies of the phenomenology and neurobiology of childhood-onset schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 105 publications
3
90
0
1
Order By: Relevance
“…A recent longitudinal and cross-sectional analysis of subjects who later developed psychosis demonstrated significant gray matter loss in right STG (Pantelis et al 2003). Jacobsen and Rapoport (1998), in a study of childhood-onset schizophrenia, showed significantly greater decreases in right temporal lobe, bilateral STG, posterior STG, and right anterior STG volumes.…”
Section: Discussionmentioning
confidence: 94%
“…A recent longitudinal and cross-sectional analysis of subjects who later developed psychosis demonstrated significant gray matter loss in right STG (Pantelis et al 2003). Jacobsen and Rapoport (1998), in a study of childhood-onset schizophrenia, showed significantly greater decreases in right temporal lobe, bilateral STG, posterior STG, and right anterior STG volumes.…”
Section: Discussionmentioning
confidence: 94%
“…Childhood-onset of schizophrenia (COS, onset by age 12) [39] is extremely rare [12;80], whereas the incidence increases between the ages 13 to 17 years [70 ;80]. A study including COS, also termed very earlyonset schizophrenia [39], observed cognitive deficits of comparable severity to those of patients with onset of schizophrenia between the ages of 13 and 18 years [71], and consequently, no distinction is made between COS and EOS patients in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood-onset of schizophrenia (COS, onset by age 12) [39] is extremely rare [12;80], whereas the incidence increases between the ages 13 to 17 years [70 ;80]. A study including COS, also termed very earlyonset schizophrenia [39], observed cognitive deficits of comparable severity to those of patients with onset of schizophrenia between the ages of 13 and 18 years [71], and consequently, no distinction is made between COS and EOS patients in this paper. Previous controlled studies of EOS patients and adolescent patients with schizophrenia spectrum disorders have reported significant deficits in several specific cognitive functions such as speed of processing, attention, verbal memory, aspects of executive functions including mental flexibility and working memory, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients with EOS demonstrate significant cognitive impairments in specific domains, mainly general intellectual ability [36][37][38][39][40][41][42], memory [43][44][45][46][47], attention [43,48,49], and executive function [46,48,50,51]. Studying early-onset cases may provide important insights into the etiopathogenesis of the disorder [50][51].…”
Section: Children and Adolescents With Schizophreniamentioning
confidence: 99%
“…Studying early-onset cases may provide important insights into the etiopathogenesis of the disorder [50][51]. However, there has been limited research addressing impairments in social cognition in young people with schizophrenia.…”
Section: Children and Adolescents With Schizophreniamentioning
confidence: 99%